Mapping of minor quantitative trait loci (QTLs) conferring fertility restoration of wild abortive cytoplasmic male sterility and QTLs conferring stigma exsertion in rice. Issue 6 (21st October 2014) - Li, Pingbo; Su, Gongche; Feng, Fuchun; Wang, Peng; Yu, Sibin; He, Yuqing; Li, J.‐K.
Abstract Cytoplasmic male sterility (CMS) hybrid rice has made a great contribution to the increase of rice yield globally. To facilitate the development of high‐quality pairs of the wild abortive (WA) male sterile and maintainer lines, the genetic basis of fertility restoration of WA‐CMS and stigma exsertion was investigated in this study using a testcross population with the WA‐CMS background. Seed‐setting rate and stigma exsertion rate were used as the indicators of the two traits, respectively. Results showed that four minor QTL regions from 9311 were responsible for the variation of seed‐setting rate, while a few minor QTLs and epistatic QTL pairs influenced stigma exsertion rate. These results would be of great use in the development of high‐quality pairs of WA male sterile and maintainer lines in rice.